2014
DOI: 10.1007/s00439-014-1504-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of enamel matrix genes on dental caries are moderated by fluoride exposures

Abstract: Dental caries (tooth decay) is the most common chronic disease, worldwide, affecting most children and adults. Though dental caries is highly heritable, few caries-related genes have been discovered. We investigated whether 18 genetic variants in the group of nonamelogenin enamel matrix genes (AMBN, ENAM, TUFT1, and TFIP11) were associated with dental caries experience in 13 age- and race-stratified samples from six parent studies (N=3,600). Linear regression was used to model genetic associations and test gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Although they all coexist in caries aetiology, the research studies usually focus on one of these components. Only a small number of studies was dedicated to analysing the interactions of genetic and environmental factors [Wang et al, 2012b;Chaussain et al, 2014;Abbasoğlu et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Future studies should associate some further information, such as metagenomics, protein-protein interaction, and gene expression, as they may be linked with caries Nibali et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they all coexist in caries aetiology, the research studies usually focus on one of these components. Only a small number of studies was dedicated to analysing the interactions of genetic and environmental factors [Wang et al, 2012b;Chaussain et al, 2014;Abbasoğlu et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Future studies should associate some further information, such as metagenomics, protein-protein interaction, and gene expression, as they may be linked with caries Nibali et al, 2016].…”
Section: Discussionmentioning
confidence: 99%
“…Authors of some studies included in the review observed the SNP phenomenon in genes involved in amelogenesis [Slayton et al, 2005;Deeley et al, 2008;Patir et al, 2008Kang et al, 2011;Olszowski et al, 2012;Shimizu et al, 2012;Tannure et al, 2012a, b;Wang et al, 2012b;Gasse et al, 2013;Chaussain et al, 2014;Duverger et al 2014;Abbasoğlu et al, 2015;Anjomshoaa et al, 2015;Shaffer et al, 2015;Yildiz et al, 2016]. Amelogenesis is a genetically controlled process of enamel development.…”
Section: Discussionmentioning
confidence: 99%
“…Home water source fluoride concentration was dichotomized as greater than 0.7 ppm versus less than 0.7 ppm, representing sufficient and insufficient fluoride concentrations, respectively. Tooth brushing frequency was dichotomized as daily or more frequent tooth brushing versus less frequent than daily brushing, which reflects the consensus in the literature that at least daily brushing is needed 33 , and is consistent with the dichotomization used in previous studies 9, 27, 34 .…”
Section: Methodsmentioning
confidence: 99%
“…In light of recent results documenting gene-by-fluoride exposure interaction effects on dental caries 26, 27 , we also tested for interaction effects with the two fluoride exposures in the samples of sufficient size for which fluoride exposure data were available (i.e., COHRA1 white adults and COHRA1 white children). These fluoride exposures were dichotomized measures of home water source fluoride (<0.7 ppm vs. ≥0.7 ppm) and tooth brushing frequency (once or more per daily vs. less often than once per day).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation